Extreme Types of Tourism in the Daily Activities of Local Communities - Кізюн, Алла Григорівна (Київський національний університет імені Тараса Шевченка, 2022)
The spontaneous development of extreme types of tourism is not always correlated with the established life of local communities, which can lead to conflict situations. The aim is to analyze the peculiarities of the development of extreme types of tourism and the possibilities of their adaptation to the daily activities of local communities. Methodology: the research was carried out using a comprehensive analysis of materials of field tourism and landscape research during 2015-2020, the principles of historicism, combination and methods of GIS technologies. Results: substantiated the existence of three tourist and recreational areas confined to the Southern Bug Valley: Pechera-Sokilets, Gaivoron and Mygiya, as well as some areas in the recreational development of which certain types of extreme tourism are gradually becoming leading. For the Pechera-Sokilets tourist-recreational area the map of possibilities of development of separate kinds of extreme tourism depending on its modern landscape structure is concluded. Scientific novelty – for the first time it was researched and substantiated that within the local communities the territories of which are confined to river valleys, the tourist and recreational sphere has become profitable for the last ten years. In its structure began to actively develop previously uncharacteristic types of extreme tourism. The dependence of the development of these types of tourism on the landscape structure of the territory of local communities is shown. Practical significance – recommended to twelve local communities territorially confined to the valleys of the Southern Bug River, possible directions and importance of the development of extreme types of tourism in their daily economic activities. Areas where the development of certain types of extreme tourism will be most effective in the process of building local communities.

Стихійний розвиток екстремальних видів туризму не завжди корелюється з усталеним життям місцевих громад, через що можливі конфліктні ситуації. Мета – здійснити аналіз особливостей розвитку екстремальних видів туризму та можливостей їх адаптації до повсякденної діяльності місцевих громад. Методика: дослідження здійснено із застосуванням комплексного аналізу матеріалів польових туристично-ландшафтознавчих досліджень упродовж 2015-2020 рр., принципів історизму, сумісництва та методів ГІС-технологій. Результати: обґрунтовано наявність трьох туристично-рекреаційних ділянок, приурочених до долини Південного Бугу: Печеро-Сокілецької, Гайворонської та Мигійської, а також окремих територій, в рекреаційному освоєнні яких окремі види екстремального туризму поступово стають провідними. Для Печеро-Сокілецької туристично – рекреаційної ділянки укладено картосхему можливостей розвитку окремих видів екстремального туризму у залежності від її сучасної ландшафтної структури. Наукова новизна – вперше досліджено та обґрунтовано, що у межах місцевих громад, території яких приурочені до долин річок, туристично-рекреаційна сфера за минулі десять років стала прибутковою. У її структурі активно почали розвивати непритаманні раніше види екстремального туризму. Показано залежність розвитку цих видів туризму від ландшафтної структури території місцевих громад. Практична значимість – рекомендовано дванадцятьом місцевим громадам територіально приуроченм до долини річки Південний Буг, можливі напрями і значимість розвитку екстремальних видів туризму у їх повсякденній господарській діяльності. Виокремлено ділянки, де розвиток окремих видів екстремального туризму буде найбільш ефективним у процесі розбудови місцевих громад.
Екстремальні види туризму у повсякденній діяльності місцевих громад
Keywords: долина Південного Бугу; місцеві громади; екстремальні види туризму; розвиток; Southern Bug valley; local communities; extreme types of tourism; development